2020
DOI: 10.3390/su12010365
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes in the Built Environment Characteristics and Urban Heat Island Effect in a Medium-Sized City, Chiayi City, Taiwan

Abstract: This study took Chiayi City—a tropical, medium-sized city—as an example to investigate the urban heat island (UHI) effect using mobile transects and built environment characteristics in 2018. The findings were compared to those from a study in 1999 to explore the spatiotemporal changes in the built environment characteristics and UHI phenomenon. The result for the UHI intensity (UHII) during the day was approximately 4.1 °C and at midnight was approximately 2.5 °C. Compared with the survey in 1999, the UHII du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…A greater degree of centralization shows many city hotspots and thus the higher UHI levels. This dependence is built by spatially complex street layouts with a high degree of irregularities, with more intersections, greater density of impervious surfaces, a more significant number and density of buildings with irregular distribution and shapes, and the related anthropogenic heat [ 185 , 186 , 187 ] characteristic for a centralized city. This description perfectly reflects the center’s image of an old and large city [ 136 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A greater degree of centralization shows many city hotspots and thus the higher UHI levels. This dependence is built by spatially complex street layouts with a high degree of irregularities, with more intersections, greater density of impervious surfaces, a more significant number and density of buildings with irregular distribution and shapes, and the related anthropogenic heat [ 185 , 186 , 187 ] characteristic for a centralized city. This description perfectly reflects the center’s image of an old and large city [ 136 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
“…On the other hand, a 1% reduction may cause a decrease in the night-time near-surface air temperature by 0.1 °C [ 292 ]. Urbanization degree is proportional to the distance from the city center [ 187 ] and size-dependent urban area [ 172 ]. It is also inversely proportional to the greenery area [ 293 , 296 ].…”
Section: Discussion and Urban Design Strategy Recommendationsmentioning
confidence: 99%
“…Tinjauan data iklim Badan Meteorologi, Klimatologi, dan Geofisika (BMKG) menunjukkan kondisi iklim di Kota Palembang tahun 2019 bervariasi terutama suhu udara. Data suhu udara dari Stasiun Klimatologi Palembang (Kenten) ratarata suhu udara minimum 24,37 o C, maksimum 33 Perbedaan suhu udara pada pusat kota dan pinggir kota dapat merujuk pada efek Urban Heat Island (UHI) yang dapat didefinisikan suatu kondisi dimana suhu udara pada perkotaan lebih tinggi daripada suhu udara di sekitarnya (Huang et al, 2020). Perbedaan suhu udara ini berkaitan secara langsung dengan tutupan lahan, suhu udara cenderung lebih rendah pada tutupan lahan berupa vegetasi di banding pada kondisi tutupan lahan lainnya (Imran et al, 2019).…”
Section: Kotaunclassified
“…It has been confirmed that, compared to the effects of global warming, Heat Islands and LST affected by built-up environments have more serious and profound effects at local scales [27][28][29]. Even if the global climate does not warm up, urban environments are currently facing the problem of rising temperatures [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%